Icariin induces S-phase arrest and apoptosis in medulloblastoma cells - Sun, Y; Sun, X-H; Fan, W-J; Jiang, X-M; Li, A-W (Cellular and Molecular Biology, 2016)
Medulloblastoma is the most common type of malignant brain tumor in children. Despite a relatively high long-term survival rate, complications still represent great burden for the majority of patients receiving traditional therapy. Therefore, the development of new effective treatments and drugs is urgently needed. A cell counting kit-8 (CCK-8) and colony formation assay were used to evaluate medulloblastoma cell proliferation and colony formation, respectively. Cell cycles and apoptosis were assessed by flow cytometry. A western blot was performed to determine the levels of protein expression. Axenograft model of medulloblastoma was established to evaluate the in vivo anticancer effects of icariin. The CCK-8 assay showed that icariin decreased cell viability in a dose- and time-dependent manner. The colony formation assay indicated that icariin potently inhibited the colony formation ability of Daoy and D341 cells. Icariin-induced proliferation inhibition may be due to S-phase arrest in medulloblastoma cells. In addition, icariin induced apoptosis in a dose-dependent manner, as shown by the results of annexin V/propidium iodide (PI) double staining and Hoechst 33342 staining. Icariin progressively inhibited tumor growth and induced apoptosis in a mouse model. Moreover, cell cycle regulators Cyclin A, CDK2, and Cyclin B1, and apoptosis-related proteins caspase-3, caspase-9, poly (ADP-ribose) polymerase (PARP), and Bcl-2 were modulated in response to treatment with icariin in vitro and in vivo. Our results suggest that icariin may exert anticancer effects. Thus, it is a promising drug for medulloblastoma treatment.